Impacto do NaCl e do ácido salicílico exógeno na fisiologia e bioquímica da planta medicinal macela-da-terra [Egletes viscosa (L.) Less] - Batista, Valéria Chaves Vasconcelos (2019)
The Northeast of Brazil has about 25% to 30% of all saline soils of the country. Several healing plants are cultivated by natives in these regions, including the 'Macela-da-terra' [Egletes viscosa (L.) Less], an Asteraceae family group, largely consumed as teas for digestive and intestinal disorders treatment. In general, plants have developed physiological and biochemical mechanisms to alleviate deleterious effects of salt in order to maintain regular growth and development. Several reports have indicated the salicylic acid (SA) a plant defense phytohormone to improve tolerance to saline stress. Thus, we hypothesized that NaCl affects E. viscosa development and exogenous SA trigger metabolic pathways that help them to reduce the harmful effects of salinity. The aim of this work was to evaluate the influence of two different concentrations of NaCl (40 mM and 80 mM) and the integrative impact of SA in the plant metabolism maintenance. The effects of salinity were accentuated and promoted a decrease in growth parameters (dry and fresh mass), and gas exchange (photosynthesis, conductance, transpiration and Ci/Ca), as well as pigments (chlorophyll a, b, total and carotenoids), regardless of the concentration used. Salinity also promoted an expected accumulation of sodium and decreased of potassium ions in both shoot and roots. Approximately, 20 volatile organic compounds (VOC's) were identified, the majority had their levels reduced, such as trans-pinocarveol, trans-carveol and, trans-pinocarveyl acetate. On the other hand, several metabolites such as amino acids (glutamine, proline, valine, among others) were increased. The interaction of salinity and exogenous salicylic acid did not reverse the effects of salinity on growth nor did it reconstruct VOC emission. However, all gas exchange parameters were increased maintaining photosynthesis, conductance, transpiration, and Ci/Ca, as well as roots potassium ions, in both concentrations of salt. In addition, the interaction between 40 mM of salt and SA also reduced some metabolites such as asparagine, glycine, and proline, among others, whereas at 80 mM a few metabolites were decreased as tryptophan, glycine and pyruvic acid. In conclusion, NaCl at 40 mM and 80 mM are harmful to E. viscosa, the interaction with exogenous AS acts to guarantee an accumulation of metabolites and potassium, promoting the maintenance of vital processes such as photosynthesis.